PERAN MANAJEMEN DALAM MENINGKATKAN KINERJA LEMBAGA KEUANGAN - Sholeh Wafie; Risa Umami; Yetma Sari (Cashless : Journal of Sharia Finance and Banking, 2025)
This study uses qualitative methods to determine the role of management in improving the performance of financial institutions. Specifically, this study aims to examine the role of management which includes human resource management (HR) and management control in an effort to improve employee performance to achieve goals in financial institutions. The results of the study show that the role of management that is structured, planned and can work well in a financial institution has a positive and significant effect on the performance of employees in a financial institution, namely the achievement of a company's goals. Management control is one of the references used to manage existing resources in financial institutions, so that financial institutions are able to get a good image, value and generate profits as expected by the company